“Most Rural” space — a regional-demographic justification for a spatial category - Weiß, Wolfgang (Raumforschung und Raumordnung | Spatial Research and Planning, 2002)
Funding provided under theAufbau Ost («Rebuilding the East») programme and other forms of financial transfer to theLänder (federal states) of eastern Germany have up to now been at their least effective in the area to the east of the River Elbe. Indeed, many of the instruments of both regional structure policy and economic development policy which have repeatedly proved their worth in the rural areas of the former West Germany have failed in the north-east. This area seems to be something of a bottomless pit. From a regional-demographic perspective, this region has to be clearly distinguished from more “ordinary” rural space, and assigned to a distinct new category to be termed “most rural space”.
Keywords: Article